Building mental models from multiple texts : how readers construct coherence from inconsistent sources - Saux, Gastón (2021)
Fil: Saux, Gastón. Pontificia Universidad Católica Argentina. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina